2011
DOI: 10.1111/j.1600-051x.2011.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration versus extraction and prosthetic replacement of teeth severely compromised by attachment loss to the apex: 5-year results of an ongoing randomized clinical trial

Abstract: Regenerative therapy can be applied at hopeless teeth and has the potential to change their prognosis; it is a suitable alternative to extraction of severely compromised teeth with intra-bony defects to or beyond the root apex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 52 publications
5
97
3
2
Order By: Relevance
“…Finally, active treatment for all patients in this study was completed by the end of 1994 before newer regenerative products and materials were available. As periodontal regenerative techniques evolve, the prognosis for all teeth, not only molars, will improve 49 . This alone places a greater emphasis on conveying a more accurate prognosis to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, active treatment for all patients in this study was completed by the end of 1994 before newer regenerative products and materials were available. As periodontal regenerative techniques evolve, the prognosis for all teeth, not only molars, will improve 49 . This alone places a greater emphasis on conveying a more accurate prognosis to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the five-year randomized control trial by Cortellini et al [3] concluded that regenerative therapy can be applied at hopeless teeth and has the potential to change their prognosis. Another factor that was considered was the effect of the hopeless teeth on proximal periodontium as in the past it was thought that retaining them would have a deleterious effect on the adjacent teeth.…”
Section: Discussionmentioning
confidence: 97%
“…It could be hypothesized that this heterogeneity may be explained by the fact that some studies used antibiotics (14)(15)(16)24,25,27,29,34) and others did not (10,17,23,26,28,30,35), by the variable surface treatments, inclusion of smokers (10,(14)(15)(16)(17)(23)(24)(25)28,29,34,35), initial depth of defects and number of remaining bone walls, use of placebo gel in some studies (10,15,16,27,34) and not in others (14,17,23-26,28,29,35), differences in methodological quality, in addition to other variables that could influence the results, such as the surgical technique, quality of instrumentation and biofilm control performed by the patients (45).…”
Section: Discussionmentioning
confidence: 99%